THE EFFECT OF PERCEPTION, HUMAN RESOURCES, IMPLEMENTATION OF FINANCIAL REPORT STANDARDS ON FINANCIAL MANAGEMENT IN SMALL MEDIUM MICRO ENTERPRISES - Raza, Hendra (CV. Radja Publika, 2022)
This study aims to examine the effect of perception, human resource competence, and implementation of financial reporting standards on financial management in micro, small and medium enterprises in Lhokseumawe City. Statistical analysis shows that the perception, competence of human resources and the implementation of financial reporting standards have a significant effect on the financial management of Micro, Small and Medium Enterprises in Lhokseumawe City. The results of this study provide useful information and valuable insights for MSMEs and can determine the magnitude of the role of perceptions, human resource competencies, implementation of financial reporting standards and financial management in maintaining or developing businesses, so as to increase innovation and be pro-active in managing SMEs so that they are able to face competition.